An evaluation of the severity and progression of epistaxis in hereditary hemorrhagic telangiectasia 1 versus hereditary hemorrhagic telangiectasia 2. (15th September 2015) - Hunter, Benjamin N.; Timmins, Benjamin H.; McDonald, Jamie; Whitehead, Kevin J.; Ward, P. Daniel; Wilson, Kevin F.
Abstract : Objectives/Hypothesis: Hereditary hemorrhagic telangiectasia (HHT) is an autosomal dominant vascular dysplasia whose hallmark symptom is spontaneous recurrent epistaxis. Two major genetic subtypes of this syndrome are HHT1 and HHT2. Severity of epistaxis ranges from occasional low‐volume bleeding to frequent large‐volume hemorrhage. This study evaluated the severity and progression of epistaxis in HHT1 versus HHT2. Study Design: Retrospective cohort study. Methods: A retrospective chart review was performed for 183 genotyped HHT patients seen at our center from 2010 to 2013. Data collected included epistaxis severity score (ESS), age of epistaxis onset, number and type of treatments, age at which treatments were sought, complete blood count values, ferritin, number of telangiectases, blood transfusions, iron therapy history, and patient demographics. Results: 115 subjects with HHT2 were compared to 68 with HHT1. Subjects with HHT2 had a higher ESS compared to HHT1 ( P  = .043) and a later age of onset of epistaxis ( P  = .005). HHT2 subjects were more likely to use oral iron ( P  = .032) and were more likely to seek interventions to control their epistaxis ( P  = .029). Conclusions: HHT2 is associated with more severe epistaxis and a subsequent higher rate of interventions, requiring more aggressive therapy as compared to HHT1. Level of Evidence: 4 Laryngoscope, 126:786–790, 2016